How Instructors Initially Viewed Teaching Online in Higher Education in the UK During the COVID-19 Pandemic - Zhao, Xin; Kung, Michael; Cai, Liang (Learning Technologies and Systems, 2021)
Learning and teaching in higher education institutions around the world have been heavily affected by the outbreak of COVID-19 since the fall of 2019. Teachers were suddenly told to convert their classes online and to be prepared to teach virtually. An online focus group (n = 9) was conducted during the initial period of lockdown in the UK at the end of March 2020 to find out about their teaching experiences of transition into online education. A number of challenges were identified in both synchronous and asynchronous teaching processes, including unfamiliarity with the learning management system, privacy concerns, student engagement, preparation time and technological issues. A set of best practices was developed for instructors teaching online during the COVID-19 pandemic.